Effect of Cinnamaldehyde Addition on Zebrafish (Danio rerio) Eggs Against Streptococcus agalactiae Infection - Asthervina Widyastami Puspitasari; Diana Arfiati; Shao-Yang Hu (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Brawijaya, 2017)
In this study, the effect of cinnamaldehyde (CA) towards Streptococcus agalactiae on zebrafish egg were investigated. To obtain the optimal concentration, CA and S. agalactiae were tested by short-term effects assay. Fresh zebrafish egg, CA and S. agalactiae were observed in different groups, single and mix treatment. The result showed that the larval survival rate (%) of single CA concentration (2.5 and 5 µg mL-1) were not significantly different compared to the control, with the value 94 ± 2.8% and 93 ± 3.3% respectively. Meanwhile, the single S. agalactiae concentration (109 and 1010 CFU mL-1) were significantly different in comparison to the control with the value 73 ± 2.1% and 6 ± 2.5%. Mix groups, larval survival rate (%) value were significantly different with the best combination value was 17 ± 4.7% at 5 µg mL-1 of CA and 109 CFU mL-1 of S. agalactiae. Even though CA may potential for zebrafish egg shelter against S. agalactiae infection. But a mixture (CA and S. agalactiae) treatments were not recommended for this study because the low value was shown compared to the single treatments. This possibility may occur because of the debris formation of two substances which leads to the poor environment and causes to low fish larval survival rate (%) value. For further study, the water quality assay is needed.